HOW INDONESIAN STATE-OWNED ENTERPRISES CHOOSE THEIR AUDITOR? - Amilia Zulfa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
As a tool to ensure the credibility of financial reports, appointing an external auditor on state-owned enterprises (SOE) is an exciting topic of study since SOE acts as an agent of development that pursues profit only. This study aims to investigate the behavior of Indonesian SOE in the selection of quality auditors by focusing on the determinants of state ownership, size, and complexity. Using a sample of central SOE and local SOE listed on the Indonesia Stock Exchange in 2014-2020, hypothesis testing was carried out using the logistic regression method. The results show that state ownership is negatively correlated with the appointment of Big-4 auditors. Meanwhile, this study reveals that both size and complexity firm variables are positively correlated with the work of Big-4 auditors.